Fundamentalist, Jurisprudential and Intentional Rules: Types, Differences between them, and their Validity for Deriving Legal Rulings - Agah, Housin Mohammad (Journal of Islamic Sciences, 2025)
This is a comparative study of jurisprudential, fundamentalist and intentional rules. It aims to distinguish between the three rules, clearly, by defining the three rules, and indicating the similarities between them, the basic differences that distinguish each of them, the extent of the authenticity of each of them, and which are suitable for deriving rulings, with accuracy, following the descriptive analytical approach and the deductive approach, the result of which is to prove the role of intentional rules in directing and controlling ijtihad, the validity of the fundamental rules to derive rulings, and the invalidity of jurisprudential rules for any of the foregoing.